ANALYSIS OF STUDENT LEARNING DIFFICULTY DURING ONLINE LEARNING (International Conference on Social and Islamic Studies, 2022)
The purpose of this study was to find out the forms of student learning difficulties during online learning and the factors causing student learning difficulties during online learning in the Madrasah Ibtidaiyah Teacher Education Study Program, Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. This type of descriptive research was conducted in the Madrasah Ibtidaiyah Teacher Education Study Program, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar with the research subject being PGMI B class class 2021 students. Data collection techniques were carried out using interviews and documentation. Data were analyzed using descriptive analysis. The results showed that the forms of learning difficulties in PPKn courses experienced by students were: 1) Difficulties in understanding and mastering the material (level of mastery) 2) Difficulties in answering questions (slow learner); (2) Factors that cause learning difficulties during online learning are factors that come from within the student (lack of learning motivation) and factors that come from outside the student's self (environmental conditions, networks and learning media). The results of this study imply that online learning has a risk of learning difficulties for students if it is not matched by learning motivation from students, network infrastructure from the government or institutions and media or learning tools from lecturers.